Depression and its associated factors among secondary school students in Malaysia - Abd Latiff, Latiffah; Tajik, Esra; Ibrahim, Normala; Abubakar, Azrin Shah; Albar Ali, Shirin Shameema (Southeast Asian Ministers of Education Organisation, 2016)
Research in the field of factors associated with depression among adolescents is lacking in Malaysia. The aims of the present study were to assess the current prevalence of depression and its related factors among secondary school students in Pasir Gudang, South Malaysia. In this cross sectional study, 2,927 secondary school students (13-17 years old) from urban areas were screened for symptoms of mental disorder as well as demographic and risk behaviors using a validated Depression, Anxiety and Stress Scale (DASS) 12 questionnaire. The majority of the respondents (53.8%) were Malay, of which 53.1% were female. Symptoms of mild depression were found in 33.2% of the respondents, while the prevalence of the symptoms of moderate, severe, and extremely severe depression was 21.5%, 18.1%, and 3.0%, respectively. Logistic regression suggested that participants who were Chinese or had a lower average grade were three times more likely to have depression, while those who came from a single-parent family were twice as likely to have this condition. This study indicated that academic performance and risk behaviors along with the demographic characteristics are important contributors to adolescent depression.